"Je suis en terrasse": Political Violence, Civilizational Politics, and the Everyday Courage to Be. Issue 2 (18th May 2017) - Browning, Christopher S.
Abstract : Following the attacks against the Paris offices of the satirical magazine Charlie Hebdo in January 2015 and the subsequent acts of political violence in Paris the following November, a number of memes spread swiftly across social media. Most notable of these were proclamations of " Je suis Charlie, " " Je suis Paris, " " Je suis en terrasse, " and tricolorizing one's Facebook profile page. Although there are various ways by which this phenomenon might be explained, this article argues that, at least for some people, they seem to have operated as key mechanisms by which individuals/society sought to reestablish what Tillich calls "the courage to be, " and which in more contemporary terminology might be labeled a sense of ontological security—the ability to go on in the face of what would otherwise be debilitating anxieties of existential dread. The article argues the memes did this through a number of mechanisms. These included establishing a sense of vicarious identification with the victims; embracing increased levels of danger and seeking to confront the question of mortality head on; reasserting a sense of community and home via the reinstantiation of everyday routines now ascribed with enhanced political and existential significance; and reaffirming a new civilizationally inflected self‐narrative.